Cytokine adsorption in patients with post-cardiac arrest syndrome after extracorporeal cardiopulmonary resuscitation (CYTER): a single-centre, open-label, randomised, controlled trial - Supady, Alexander; Zahn, Timm; Kuhl, Moritz; Maier, Sven; Benk, Christoph; Kaier, Klaus; Böttiger, Bernd W.; Bode, Christoph; Lother, Achim; Staudacher, Dawid L.; Wengenmayer, Tobias; Duerschmied, Daniel (Resuscitation, 2022)
AIM: To investigate the effect of cytokine adsorption in patients receiving extracorporeal cardiopulmonary resuscitation (ECPR) after cardiac arrest. - METHODS: CYTER was a single-centre, open-label, randomised, controlled trial. Patients selected for ECPR at the University Medical Center Freiburg (Freiburg, Germany) were assigned to extracorporeal membrane oxygenation (ECMO) support with or without cytokine adsorption (1:1) using the CytoSorb adsorber, incorporated into the ECMO, replaced every 24 hours, and removed after 72 hours. The primary endpoint was serum interleukin (IL)-6 concentration at 72 hours (intention-to-treat analysis). Secondary endpoints included 30-day survival, vasopressor support and biomarkers of end-organ injury. - RESULTS: Of 50 patients enrolled in the trial, 26 (52%) were treated with cytokine adsorption and 24 (48%) without. Nine patients were excluded (informed consent could not be obtained); 41 patients were therefore included in the primary analysis. Median IL-6 levels (IQR) decreased from 408.0(93.4-906.5) to 324.0 (134.3-4617.3) pg/mL and increased from 133.0 (56.2-528.5) to 241.0 (132.8-718.0) pg/mL in the cytokine adsorption and control group, respectively (linear regression for treatment [cytokine adsorption vs control]: p = 0.48). Three (14%) of 22 patients treated with cytokine adsorption and 8 (42%) of 19 patients treated without cytokine adsorption survived to day 30 (HR = 1.85, 95% CI 0.86-4.01; p = 0.10). Vasopressor support and NSE, S100b, troponin T, CRP and PCT levels were similar between groups. - CONCLUSION: Cytokine adsorption in patients receiving ECPR did not reduce serum IL-6 and had no significant effect on survival, vasopressor support, or biomarkers of injury. - CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov: NCT03685383.